2022
DOI: 10.1021/jacs.1c11874
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Activated Fluorescence vs Long Persistent Luminescence in ESIPT-Attributed Coordination Polymer

Abstract: Excited-state intramolecular proton transfer (ESIPT) molecules demonstrating specific enol-keto tautomerism and the related photoluminescence (PL) switch have wide applications in displaying, sensing, imaging, lasing, etc. However, an ESIPT-attributed coordination polymer showing alternative PL between thermally activated fluorescence (TAF) and long persistent luminescence (LPL) has never been explored. Herein, we report the assembly of a dynamic Cd­(II) coordination polymer (LIFM-101) from the ESIPT-type liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
75
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 49 publications
0
75
0
Order By: Relevance
“…4 In 2022, Su et al reported an ESIPT-attributed Cd-MOF which achieved thermally activated fluorescence and long persistent luminescence. 5 As a common type of industrial ingredient, phenylenediamine was added to lots of chemical products. When the content of phenylenediamine is too higher, environmental security and human health might be damaged.…”
Section: Introductionmentioning
confidence: 99%
“…4 In 2022, Su et al reported an ESIPT-attributed Cd-MOF which achieved thermally activated fluorescence and long persistent luminescence. 5 As a common type of industrial ingredient, phenylenediamine was added to lots of chemical products. When the content of phenylenediamine is too higher, environmental security and human health might be damaged.…”
Section: Introductionmentioning
confidence: 99%
“…Each Cu 2+ is pentacoordinated to four O atoms from four MBA linkers with the bond length of 1.975(2), 1.969(2), 1.977(2) and 1.969(2) Å for Cu-O1, Cu-O2, Cu-O3 and Cu-O4, respectively. The angles of O1-Cu1-O2, O3-Cu1-O4, O1-C1-N1 were 88.31 (8), 89.35(0) and 100.94(0)°, respectively. The distance between two copper atoms is 2.641 Å, suggesting existence of Cu-Cu bonding interaction.…”
Section: Resultsmentioning
confidence: 96%
“…[1,2] Reasonable ligand design and selection of metal ions can realize multi-functionalization of CP materials. [3,4] These CPs have been applied to the fields of luminescence, [5][6][7][8][9] sensing, [10][11][12][13] catalysis, [14][15][16] etc. The coordination groups in the ligands are usually pyridine, imidazole, hydroxyl, carboxyl, sulfhydryl, methylthio units containing nitrogen, sulfur and oxygen atoms, while the metal ions are usually transition, rare-earth, and a small number of main-group metals.…”
Section: Introductionmentioning
confidence: 99%
“…20 references. 38,66–88 For the most part, these complexes are based on aromatic carboxylic acids ( e.g. 3-hydroxy-2-quinoxalinecarboxylic acid, 2,5-dihydroxyterepthalic acid) and 2-(1 H -imidazol-2-yl)phenol derivatives decorated by aromatic carboxylic acid groups.…”
Section: Introductionmentioning
confidence: 99%
“…3-hydroxy-2-quinoxalinecarboxylic acid, 2,5-dihydroxyterepthalic acid) and 2-(1 H -imidazol-2-yl)phenol derivatives decorated by aromatic carboxylic acid groups. 66–88 Metal ions used in the synthesis of ESIPT-complexes are mostly the ions of divalent metals of the second and twelfth groups of the periodic table (Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ , Zn 2+ , Cd 2+ ) and the ions of trivalent lanthanides (Sm 3+ , Eu 3+ , Tb 3+ , Gd 3+ , Er 3+ , Nd 3+ ). Metal–organic frameworks (MOFs) based on divalent ions show fluorescence.…”
Section: Introductionmentioning
confidence: 99%